VDAC2 enables BAX to mediate apoptosis and limit tumor development. Issue 1 (December 2018) - Chin, Hui; Li, Mark; Tan, Iris; Ninnis, Robert; Reljic, Boris; Scicluna, Kristen; Dagley, Laura; Sandow, Jarrod; Kelly, Gemma; Samson, Andre; Chappaz, Stephane; Khaw, Seong; et al.
Abstract Intrinsic apoptosis is critical to prevent tumor formation and is engaged by many anti-cancer agents to eliminate tumor cells. BAX and BAK, the two essential mediators of apoptosis, are thought to be regulated through similar mechanisms and act redundantly to drive apoptotic cell death. From an unbiased genome-wide CRISPR/Cas9 screen, we identified VDAC2 (voltage-dependent anion channel 2) as important for BAX, but not BAK, to function. Genetic deletion ofVDAC2 abrogated the association of BAX and BAK with mitochondrial complexes containing VDAC1, VDAC2, and VDAC3, but only inhibited BAX apoptotic function. DeletingVDAC2 phenocopied the loss ofBAX in impairing both the killing of tumor cells by anti-cancer agents and the ability to suppress tumor formation. Together, our studies show that efficient BAX-mediated apoptosis depends on VDAC2, and reveal a striking difference in how BAX and BAK are functionally impacted by their interactions with VDAC2. BAX and BAK are pro-apoptotic proteins whose activity is essential for the action of many anti-cancer drugs and to suppress tumorigenesis. Here, the authors perform a genome-wide CRISPR/Cas9 screen and identify VDAC2 as a promoter of BAX-mediated apoptosis that is important for an efficient chemotherapeutic response and to suppress tumor formation.